2022
DOI: 10.1128/mbio.00609-22
|View full text |Cite
|
Sign up to set email alerts
|

Has Epizootic Become Enzootic? Evidence for a Fundamental Change in the Infection Dynamics of Highly Pathogenic Avian Influenza in Europe, 2021

Abstract: Phylogenetic evidence from the recent resurgence of high-pathogenicity avian influenza (HPAI) virus subtype H5N1, clade 2.3.4.4b, observed in European wild birds and poultry since October 2021, suggests at least two different and distinct reservoirs. We propose contrasting hypotheses for this emergence: (i) resident viruses have been maintained, presumably in wild birds, in northern Europe throughout the summer of 2021 to cause some of the outbreaks that are part of the most recent autumn/winter 2021 epizootic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(145 citation statements)
references
References 21 publications
4
141
0
Order By: Relevance
“…The 2014-2015 viruses also reassorted soon after detection on the continent, but this reassortment was not associated with changes in mammalian pathogenicity 22 . The recently prevalent 2.3.4.4b viruses are also changing the dynamics of disease in Europe, with the potential for transition from epizootic to enzootic status 23 . Our data highlight how quickly things can change in a natural system, and the potential for further A(H5Nx) reassortment and phenotypic diversi cation will only increase as the unprecedented global distribution of these viruses broadens.…”
Section: Full Textmentioning
confidence: 99%
“…The 2014-2015 viruses also reassorted soon after detection on the continent, but this reassortment was not associated with changes in mammalian pathogenicity 22 . The recently prevalent 2.3.4.4b viruses are also changing the dynamics of disease in Europe, with the potential for transition from epizootic to enzootic status 23 . Our data highlight how quickly things can change in a natural system, and the potential for further A(H5Nx) reassortment and phenotypic diversi cation will only increase as the unprecedented global distribution of these viruses broadens.…”
Section: Full Textmentioning
confidence: 99%
“…Outbreaks of H5N8 HPAIV were, in the Far East, once terminated in spring 2021 but continuously reported in European poultry and wild birds until summer 2021 [ 7 ]. Moreover, infections with H5N1 HPAIVs, which could be generated as reassortment between H5N8 HPAIVs circulating in Europe and low-pathogenicity avian influenza viruses circulating locally, have been dominant in European countries since late spring 2021, contrary to the decrease of the reported cases of H5N8 HPAIV infections [ 8 ]. It was confirmed that two types of H5 viruses with different hemagglutinin (HA) in the genetic pool were already circulating in autumn 2021; one had been continuously present with genetic drift among the European bird population since autumn 2020, and the other, which originated in African countries but could be widely spread throughout European countries [ 8 ] had been detected since October 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, infections with H5N1 HPAIVs, which could be generated as reassortment between H5N8 HPAIVs circulating in Europe and low-pathogenicity avian influenza viruses circulating locally, have been dominant in European countries since late spring 2021, contrary to the decrease of the reported cases of H5N8 HPAIV infections [ 8 ]. It was confirmed that two types of H5 viruses with different hemagglutinin (HA) in the genetic pool were already circulating in autumn 2021; one had been continuously present with genetic drift among the European bird population since autumn 2020, and the other, which originated in African countries but could be widely spread throughout European countries [ 8 ] had been detected since October 2021. Under such a circumstance, many gene-reassorted viruses, including H5N1, were generated, and dominant H5N1 reassorted viruses were further transferred from Europe to African, North American, or Asian countries in winter 2021–2022 [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The map in Figure 4 shows the geographical distribution of all H5N1 genotypes identified in the Czech Republic during the 2021/2022 season. The index case, ID 18520/21, is the only known representative of the resident B1 lineage among the detected viruses [10]. This finding was followed by an outbreak of H5N1 LPAI in commercial geese with close phylogeny to other European H5N1 viruses of low pathogenicity found mainly in Italy.…”
Section: Resultsmentioning
confidence: 91%
“…Taken together, the data suggests that the H5N1 HPAI has circulated at the background level throughout the entire period of dominance of the A/ck/Iq/1/2020like H5N8 strains. Moreover, one subclade apparently persisted during the summer in the wild bird population in northern Europe [9,10]. Genotyping of the H5N1 strains collected from 2020/2021 indicated the wide distribution of the original A/ew/NL/2020-like genotype constellation, with reassortants having been observed since the end of September 2021 [11].…”
Section: Introductionmentioning
confidence: 99%